Evolved Developmental Niche Provision Report: Moral Socialization, Social Thriving, and Social Maladaptation in Three Countries. (April 2019) - Narvaez, Darcia; Woodbury, Ryan; Cheng, Ying; Wang, Lijuan; Kurth, Angela; Gleason, Tracy; Deng, Lifang; Gutzwiller-Helfenfinger, Eveline; Christen, Markus; Näpflin, Catherine
Evolutionary systems theory identifies niches as key developmental inheritances for animals. The human evolved developmental niche (EDN) is characterized by positive touch, responsiveness, play, and social togetherness and provides the responsive, relational dynamism that optimizes development. Cross-sectional and longitudinal studies of the human EDN have demonstrated correlations between degree of EDN consistency in early childhood and positive sociomoral development and avoidance of ill-being and misbehavior. We created a brief report of children's recent EDN experience and examined its relation to child well-being and sociomoral development. Using samples from three cultures (United States, N =574; Switzerland, N =96; China, N =382), EDN provision in the past week was related to multiple child outcomes even after controlling for parental age, education, income, responsivity, and child gender. Factor analyses indicated three sets of latent factors in each sample: Moral Socialization, Social Maladaptation, and Social Thriving. Structural equation models indicated that EDN provision significantly predicted Social Thriving in all samples beyond control variables. EDN provision may be particularly helpful in predicting optimal social development.